The Second Time Around Rambert and revivals - Mackrell, Judith 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Mark Baldwin has been making some very creative dips into the archives recently - and not just the back catalogue belonging to Rambert. After reviving Christopher Bruce's Swansong he has persuaded Siobhan Davies to bring back Carnival of the Animals, the piece she made for Second Stride in 1982.